Malmö Art Academy 2002 Yearbook. - Sandqvist, Gertrud; Bonde, Niels; Durham, Jimmie; Eriksson, Annika; Lind, Maria; Fänge, Jens; Malmö Art Academy, Malmö (Malmö : Malmö Art Academy, 2002)
Algin, Ellinor ; Bauer, Petra ; Böttcher, Ann ; Christiansen, Daniel Svarre ; Dahlström, Henrik ; Edgren, Helene ; Einhorn, Ewa ; Eklund, Cajsa ; Fransson, Beata ; Fryland, Mia ; et al.
Malmö Art Academy, 2002
kunstcatalogus